Diffraction Imaging for Exploration of Seafloor Massive Sulfide Deposits - Case Study Solwara 1 Site - Tertyshnikov, Konstantin; Pevzner, Roman; Bóna, Andrej; Alonaizi, Faisal Abdulkader; Gurevich, Boris (EAGE, 2014)
Extraction of mineral resources on land is becoming increasingly difficult. Recent discoveries of seafloor massive sulfides (SMS), which host significant amount of mineral commodities, appear as a new potential offshore mining sector. The marine 3D seismic exploration survey was carried out over a seafloor massive sulfide deposit at Solwara 1 site in the Bismark Sea, west of New Ireland, Papua New Guinea. Despite the fact that all prospective sulfide mineralization zones are concentrated close to the seafloor, knowledge of internal deep geological structures of seabed volcanic ridges and their genesis is important for understanding of the formation of mineral deposits. The steered migration with diffractions was applied to 3D seismic volume to emphasize deep geological structures and to enhance the signal to noise ratio of the seismic images. The post-stack steered migration utilizes coherency attributes obtained by a diffraction imaging algorithm in 3D to weight or steer the main Kirchhoff summation. The application of the steered migration to the investigation of the modern subduction zone at the Solwara 1 mine enhanced the signal to noise ratio of the final migrated images and helped to understand the formation mechanisms of seabed deposits in the region by exploring the deep structures.